TATWIRU KITABI "CINTA BERBAHASA ARAB" AL JUZ AL AWWAL ALA ASASIL MUHAKAH LIL MADRASAH AL IBTIDAIYYAH - Nurul Hikmah (Jurnal Al-Maqoyis, 2019)
The development of Arabic teaching materials is very important so that the material taught is in accordance with the goals and learning outcomes of students. the author uses research and development methods in developing teaching materials at madrasah ibtidaiyah. The material developed by the researcher is the Kitabah learning material in the first grade of Madrasah Ibtidaiyah in order to train students' ability to write Arabic. Hijaiyah letters are letters or characters used in Arabic that generally known to be 28 letters, and have different shapes according to the position of aletters in a word that is at the beginning, in the middle, at the end, and the original letters that stand alone. students are required to be able to write Arabic correctly according to the rules of writing Arabic letters. The material must be accompanied by enough exercises. The design of the Arabic language teaching material model that will be developed in this study consists of: (1) needs analysis, (2) the process of drafting a model consisting of an analysis of learning conditionsnamely the analysis of learning objectives and sources, the development steps consisting of:from the activities of formulating SK-KD, compiling the syllabus, determining the method and media and develop evaluation instruments and measures for measuring results study. (3) compiling a draft of teaching materials consisting of an introduction, instructions for using materials and book instructions, analysis of learning programs and learning activities. All of these were formulated by the researchers in a single unit of teaching material consisting of: content, exercises and evaluations. The design of this teaching material model is only limited to designs compiled based on research introduction To test the effectiveness of the success of this material against students' language skills need further research.